Proceeding of the 2nd Temengor Scientific Expedition 2012 22-25 August 2013 (Pulau Banding Foundation, 2013)
It is here, at Pulau Banding, that the foundation began its mission to improve the lives of the region's indigenous inhabitants, while encouraging the continuation of this community's respectful relationship with nature. The challenge was, and remains, to balance Forest with Development and thereby minimize undue impact toi this 130 million year old green jewel.